Views on Europe: gender historical and postcolonial perspectives on journeys - Riettiens, Lilli; Riettiens, Lilli; Kleinau, Elke; Kleinau, Elke (Studies in the history of education and culture, 2022)
The history of travel has long been constructed and described almost exclusively as a history of "European", male mobility, without, however, explicitly making the gender and whiteness of the travellers a topic. The anthology takes this as an occasion to focus on journeys to Europe that gave "non-Europeans" the opportunity to glance at "Europe" and to draw a picture of it by themselves. So far, little attention has been paid to the questions with which attributes these travellers endowed "Europe" and its people, which similarities and differences they observed and which idea(s) of "Europe" they produced. The focus is once again on "Europe", but not as the starting point for conquests or journeys. From a postcolonial and gender historical view, the anthology’s contributions rather juxtapose (self-)representations of "Europe" with perspectives that move in a field of tension between agreement, contradiction and oscillation.
Keywords: Europe -- Civilization; Europe -- Description and travel; Europe - Civilisation; Europe - Descriptions et voyages; Europe; Aufsatzsammlung; Geschichte; Reiseliteratur; Nationalcharakter; Europabild